Nuclear families and radical feminism in 2000's American TV series. (1st June 2019) - Morin, Céline
Representations of the nuclear family have undergone significant redefinitions on American television over the last fifteen years: recent 40-something heroines are examining the slow decline of the nuclear family, aided by the return of radical feminism. This article analyses this critical New Wave, which appeared on television with Desperate Housewives (2004–2012) and continues in dramas such as The Good Wife (2009–2016) and dramedies such as The Big C (2010–2013), Nurse Jackie (2009–2015) and Weeds (2005–2012). The complexity of television's treatment of the explosion of the nuclear family is due to the fact that TV series marry a broken – shattered, even – dream with its residual forms: families are falling apart and yet the heroines are confronted with the pressing need to continue upholding its social representation. To escape traditional roles, women are according emotions a new place and witnessing a redistribution of skills in various forms. In place of the predetermined structure of the nuclear family, intimate public spheres are emerging, where women are establishing themselves as long-oppressed individuals on the road to an emancipation that can occur only in the context of a fundamental rethinking of the organization of the private sphere.